2014
DOI: 10.1128/jvi.01713-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a High-Efficiency Baculovirus DNA Replication Origin That Functions in Insect and Mammalian Cells

Abstract: The p143 gene from Autographa californica multinucleocapsid nucleopolyhedrovirus (AcMNPV) has been found to increase the expression of luciferase, which is driven by the polyhedrin gene promoter, in a plasmid with virus coinfection. Further study indicated that this is due to the presence of a replication origin (ori) in the coding region of this gene. Transient DNA replication assays showed that a specific fragment of the p143 coding sequence, p143-3, underwent virus-dependent DNA replication in Spodoptera fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Baculoviruses have been also explored as a possible gene delivery vector system for vertebrate cells [ 9 12 ]. These viruses may be ideal for gene therapy because their viral promoters are almost silent in mammalian cells, and the budded viral form is harmless to the environment [ 13 16 ]. Autographa californica multicapsid nucleopolyhedrovirus ( Ac MNPV), a widely studied baculovirus, is as a promising gene therapy vector [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baculoviruses have been also explored as a possible gene delivery vector system for vertebrate cells [ 9 12 ]. These viruses may be ideal for gene therapy because their viral promoters are almost silent in mammalian cells, and the budded viral form is harmless to the environment [ 13 16 ]. Autographa californica multicapsid nucleopolyhedrovirus ( Ac MNPV), a widely studied baculovirus, is as a promising gene therapy vector [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from hr s, other ORIs containing tandemly repeated sequences have been characterized in AcMNPV [39,42], SpliMNPV [70], SeMNPV [58,71,72], OpMNPV [33,59], and CrleGV [60]. Also, in AcMNPV, two other kinds of non- hr ORIs have been described: Early promoters [34], and a segment of the DNA helicase ORF [35]. In our work, 12 different sequences of AgMNPV classified as intergenic and intragenic regions were detected and named ORI-igrs and ORI-grs, according to the presence of putative functional early promoters or the presence of fragments of ORFs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, homologous regions ( hr s) [30,31], non- hr sequences [32,33] and early promoters [34] have been identified as causing the infection-dependent replication of plasmids. Wu et al [35] identified a different non- hr ORI inside a core gene of AcMNPV ( p143 or DNA helicase), broadening the spectrum of sequences involved in this function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one non- hr ori was found in the AcMNPV genome, and it showed some distant structural homology to consensus eukaryotic ori s ( DePamphilis 1993 , Lee and Krell 1994 ). Surprisingly, the p143 -3.2a ori of AcMNPV was found to function as an efficient ori in mammalian cells without the need for any viral proteins ( Wu et al. 2014 ).…”
mentioning
confidence: 99%